2017
DOI: 10.1080/10826084.2017.1355388
|View full text |Cite
|
Sign up to set email alerts
|

The Social Context of Adolescent Co-Use of Cigarillos and Marijuana Blunts

Abstract: All participants reported smoking cigarillos for use as a tobacco product, averaging 13 per week. Twenty-five (83%) also reported using cigarillos to smoke marijuana blunts. A preference for group smoking and product sharing, and the belief that cigarillos extend the high of marijuana were found to promote the co-use of these products. Cigarillos were also found to be used as a substitute for blunts when marijuana was unavailable or when its use was being restricted or monitored. Conclusions/Importance: This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…Blunting a cigar is a popular form of marijuana use among adolescents. 1 Blunting, or making a blunt, is a process whereby some or all of the tobacco is removed from a cigar product (eg, large cigar, little cigar, cigarillo, or tobacco rolling paper), then replaced with marijuana and smoked. 2,3,4 Estimates suggest that 12% to 19% of adolescents have smoked a blunt in the past month.…”
Section: Introductionmentioning
confidence: 99%
“…Blunting a cigar is a popular form of marijuana use among adolescents. 1 Blunting, or making a blunt, is a process whereby some or all of the tobacco is removed from a cigar product (eg, large cigar, little cigar, cigarillo, or tobacco rolling paper), then replaced with marijuana and smoked. 2,3,4 Estimates suggest that 12% to 19% of adolescents have smoked a blunt in the past month.…”
Section: Introductionmentioning
confidence: 99%
“…Two questions assessed the number of cigarillos smoked in the past 30 days. Both questions were asked separately for tipped and untipped cigarillos, since research has shown that these products may be used differently 17 29 30. First, participants were asked on how many days in the past 30 days they smoked part or all of these products.…”
Section: Methodsmentioning
confidence: 99%
“…Then participants were asked to report how many cigarillos they had smoked each day of the past week (Monday-Sunday)—both alone and in a group (if applicable). These questions were based on extant research regarding a common pattern of smoking cigarillos as they are passed around a group 17 31. Those who reported smoking cigarillos in a group were also asked how many people were typically in the group.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-participation was due to student absence on the day These modification processes may affect the perceived risks of CCLCs. Research among adults indicates that adults freak their cigar to make them healthier, 19 and blunts are considered healthier than non-modified cigars, 13,20 which could be related to a perception that marijuana is a less risky product than tobacco. 21…”
Section: Methodsmentioning
confidence: 99%